The Simplification of the following expression is;
7/8m - 4/7 - 5/6m = - 3/4
7/8m - 5/6m = -3/4 + 4/7
21m-20m/24 = -21+16/28
1/24m = -5/28
m = -5/28 ÷ 1/24
= -5/28 × 24/1
= -120/28
m = -30/7
4.3v + 10.75 - 4v = 8.11
0.3v = 8.11 - 10.75
0.3v = -2.64
v = -2.64/0.3
v = -8.8
9/7 + 9/7x - 6/7x =0
9/7x - 6/7x = - 9/7
(9-6)x /7 = 9/7
3/7x = 9/7
x = 9/7 ÷ 3/7
= 9/7 × 7/3
= 9/3
x = 3
6.9u - 2 - 3.2u - 10 = 2.8
3.7u = 2.8 - 12
3.7u = -9.2
u = -9.2/3.7
u = -2.49
8/5 = - 4a + 7/5 - 2/3a
8/5 - 7/5 = -4a - 2/3a
8-7/5 = -12a-2a/3
1/5 = -14/3a
a = 1/5 ÷ -14/3
= 1/5 × -3/14
a = -3/70
Learn more about simplification:
https://brainly.com/question/723406
#SPJ1